2015
DOI: 10.1523/jneurosci.2656-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Residual Errors in Motor Adaptation Tasks: Reversion to Baseline and Exploratory Escape

Abstract: When movements are perturbed in adaptation tasks, humans and other animals show incomplete compensation, tolerating small but sustained residual errors that persist despite repeated trials. State-space models explain this residual asymptotic error as interplay between learning from error and reversion to baseline, a form of forgetting. Previous work using zero-error-clamp trials has shown that reversion to baseline is not obligatory and can be overcome by manipulating feedback. We posited that novel error-clam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 34 publications
11
72
0
Order By: Relevance
“…Previous studies have used clamped visual feedback to induce adaptation, but their participants were not informed that feedback would be clamped; as such, the participants likely believed that changes in their behavior could affect this feedback to reinstate good task performance (Vaswani et al, 2015; Scheidt, Conditt, Secco, & Mussa-Ivaldi, 2005). A critical difference between previous clamp studies and our method is that we fully informed participants of the nature of the manipulation and asked them to ignore it.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used clamped visual feedback to induce adaptation, but their participants were not informed that feedback would be clamped; as such, the participants likely believed that changes in their behavior could affect this feedback to reinstate good task performance (Vaswani et al, 2015; Scheidt, Conditt, Secco, & Mussa-Ivaldi, 2005). A critical difference between previous clamp studies and our method is that we fully informed participants of the nature of the manipulation and asked them to ignore it.…”
Section: Discussionmentioning
confidence: 99%
“…Why would one remember an action or aiming direction that was ultimately unsuccessful (i.e., led to a target miss), as is often the case given the bias toward baseline often exhibited at asymptote (Kitago et al 2013;van der Kooij et al 2015;Vaswani et al 2015)? It is plausible that a memory for action could be formed because of strong positive reward prediction errors experienced by subjects during the initial course of adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Under this view, implicit, context-dependent learning could, for example, be achieved by proceduralization of strategies at the action selection level, in line with canonical views of skill learning (Fitts and Posner 1967;Willingham 1998). Recent findings have shown that that new policies can be learned by exploration and reinforcement (Shmuelof et al 2012;Vaswani et al 2015), and that this is closely tied to explicit strategies Holland et al 2018). A possibility is that explicit action selection tendencies may become proceduralized by associative learning.…”
Section: Discussionmentioning
confidence: 99%